A Review of Multi-objective Optimization: Methods and Algorithms in Mechanical Engineering Problems - Pereira, João Luiz Junho; Oliver, Guilherme Antônio; Francisco, Matheus Brendon; Cunha, Sebastião Simões; Gomes, Guilherme Ferreira (Archives of computational methods in engineering, 2022)
The optimization problems that must meet more than one objective are called multi-objective optimization problems and may present several optimal solutions. This manuscript brings the most important concepts of multi-objective optimization and a systematic review of the most cited articles in the last years in mechanical engineering, giving details about the main applied multi-objective optimization algorithms and methods in this field. Some of the applications that can be found in this study are: (i) problems in design optimization, (ii) problems in manufacturing: welding, machining and molding and (iii) problems in structural health monitoring. It can be seen that classic optimization methods had their importance in the past, but lost space for new algorithms that emerged with the advancement of computing, better able to deal with a greater number of variables, objectives and nonlinearities. These powerful algorithms, still little used in Mechanical Engineering, showed significant improvement where they were applied. Meta-heuristics with a posteriori decision-making techniques proved to be a modern trend in solving multi-objective problems, although it is not limited due to the constant battle of new algorithms more adapted to specific problems.